2007
DOI: 10.1002/art.22701
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of bovine synovium: Bone morphogenetic proteins 2 and 7 and transforming growth factor β1 induce the formation of different types of cartilaginous tissue

Abstract: Objective. To compare the potential of bone morphogenetic proteins 2 and 7 (BMP-2 and BMP-7) and transforming growth factor ␤1 (TGF␤1) to effect the chondrogenic differentiation of synovial explants by analyzing the histologic, biochemical, and gene expression characteristics of the cartilaginous tissues formed.Methods. Synovial explants derived from the metacarpal joints of calves were cultured in agarose. Initially, BMP-2 was used to evaluate the chondrogenic potential of the synovial explants under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
78
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 46 publications
7
78
0
1
Order By: Relevance
“…This suggests that either proliferation was not a prerequisite for chondrogenic differentiation or that IdU-labeled cells had divided very few times before CIdU was administered 8 days after surgery, so that they retained IdU beyond the period of proliferation but were negative for CIdU. Although we cannot exclude the possibility that IdU-positive chondrocytes migrated out of the articular cartilage into the synovium, our study indicated an obvious contribution of synovial cells to the process of cartilage metaplasia in synovium, in keeping with previous observations that treatment of synovial tissue explants in vitro with chondrogenic growth factors induced cartilage formation (40,41). Cartilage metaplasia was observed throughout the knee joint synovium but was much more pronounced at the transition zone where the synovium connects to the articular cartilage, mimicking the chondrophytes observed in osteoarthritis.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that either proliferation was not a prerequisite for chondrogenic differentiation or that IdU-labeled cells had divided very few times before CIdU was administered 8 days after surgery, so that they retained IdU beyond the period of proliferation but were negative for CIdU. Although we cannot exclude the possibility that IdU-positive chondrocytes migrated out of the articular cartilage into the synovium, our study indicated an obvious contribution of synovial cells to the process of cartilage metaplasia in synovium, in keeping with previous observations that treatment of synovial tissue explants in vitro with chondrogenic growth factors induced cartilage formation (40,41). Cartilage metaplasia was observed throughout the knee joint synovium but was much more pronounced at the transition zone where the synovium connects to the articular cartilage, mimicking the chondrophytes observed in osteoarthritis.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that BMP-7 interfered with caspase-mediated cell death after mechanical injury, and could play a role in inhibition of cell-cell signaling leading to apoptosis. Because there was no clear evidence of additional cells 43 participating in the repair process, our data suggest that BMP-7 allowed survival and retention of native chondrocytes that replenished and remodeled the damaged matrix. Measuring cell viability and metabolic activity per unit volume of cartilage would be a more reliable evidence of this hypothesis, but this would be technically demanding and require a larger experiment.…”
mentioning
confidence: 75%
“…43 Synovial explants treated with BMP-2 expressed the cartilage-specific markers type II collagen and proteoglycan, but by 6 weeks in culture, the authors noted the grossly hypertrophic state of the differentiated synovial cells. 44 In a more recent experiment, ATDC5 cells, a chondrogenic cell line from the AT805 mouse teratocarcinoma, were shown to have enhanced proteoglycan synthesis up to 4 weeks in cultures in which BMP-2 was stably over-expressed, but the same study found that alkaline phosphatase expression and activity also increased in response to BMP-2 in as little as 9 days. 45 Similarly, BMP-2 promoted hypertrophy of primary chondrocytes grown for 4 weeks on substrates that support three-dimensional cell morphology.…”
Section: Discussionmentioning
confidence: 98%